A198 PHARMACODYNAMIC EFFECTS OF THE ORAL, NON-STEROIDAL FARNESOID X RECEPTOR AGONIST GS-9674 IN HEALTHY VOLUNTEERS. (1st March 2018) - Myers, R P; Djedjos, C; Kirby, B; Bilin, A; Khan, M; Gosink, J; Song, Q; Srihari, R
Abstract: Background: GS-9674 is a non-steroidal Farnesoid X Receptor (FXR) agonist in development for the treatment of nonalcoholic steatohepatitis (NASH) and cholestatic liver disorders. Oral GS-9674 increased plasma fibroblast growth factor 19 (FGF19), decreased 7-α-hydroxy-4-cholesten-3-one (C4), and improved liver histology in rodent and primate models of NASH. Aims: This first-in-human study evaluated the safety, pharmacokinetics (PK), and pharmacodynamic (PD) effects of GS-9674 in healthy volunteers. Data on PD markers (FGF19 and C4), PK/PD and PD/PD relationships, and the effects of GS-9674 on serum cholesterol are presented herein. Methods: In this randomized, double-blind, placebo-controlled study, subjects received single and multiple doses (QD, 14 days) of GS-9674 (10, 30, 100, or 300 mg while fasting [N=12/cohort]) or matching placebo (N=3/cohort) with a 6-day washout between the single and multiple dose periods. Plasma FGF19 (by ELISA) and serum C4 (by LC-MS/MS) were measured over 24 hours pre-dose (Day -1) and after single (Day 1) and multiple dose administration (Day 20). PD parameters for FGF19 and C4 (AUC2-8hr and Cmax or Cmin ) were calculated and normalized to Day -1 values. Changes in serum cholesterol were also assessed. Results: PD responses to GS-9674 observed on Day 1 and Day 20 were comparable. GS-9674 doses ≥30 mg significantly increased FGF19 and reduced C4 exposure compared to placebo (Table). Changes in FGF19 and C4 AUC2-8hr were inversely correlated (r= -0.335 p =0.02). While FGF19 exposure did not show dose-dependent changes, changes in C4 AUC2-8hr were inversely associated with GS-9674 AUCtau (r= -0.45 p <0.01). Effects of GS-9674 on serum cholesterol at Day 20 were mild and not significantly different from placebo. Conclusions: Oral GS-9674 administration results in increased levels of FGF19 and decreased C4 confirming its biological activity. These data support the evaluation of GS-9674 in patients with NASH and cholestatic liver disorders. Funding Agencies: Gilead Sciences, Inc.